Animals in the Qur'an - Tlili, Sarra, 1964- (Cambridge : Cambridge University Press, 2012)
"The Islamic tradition has always held animals in high esteem, deserving the same level of consideration as humans. The Qur'an opines that 'there is not an animal in the earth nor a flying creature flying on two wings, but they are people like you'. This fascinating and highly original book examines the status and nature of animals as they are portrayed in the Qur'an and in adjacent exegetical works, in which animals are viewed as spiritual, moral, intelligent and accountable beings. In this way, the study presents a challenge to the prevalent view of man's superiority over animals and suggests new ways of interpreting the Qur'an. By placing the discussion within the context of other religions and their treatment of animals, the book also makes a persuasive case for animal rights from an Islamic perspective"--
Machine generated contents note: 1. Animals outside Islamic tradition; 2. Exegesis, exegetes and relevant notions; 3. Are they inferior?; 4. Depiction of nonhuman animals in the Qur'an; 5. Humans in the Qur'an.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Animals in the Koran; Animals in the Koran; Religion; RELIGION / Islam / Koran & Sacred Writings; Electronic books